Studi komparasi fungsi traffic island Taman Rama Shinta dengan traffic island Taman Patung Tualen di Badung, Bali - Ida Bagus Kade Adi Putra; I Gusti Agung Ayu Rai Asmiwyati (Jurnal Arsitektur Lansekap, 2026)
Traffic islands serve to regulate traffic flow and provide temporary waiting spaces for pedestrians. However, there are indications of a functional shift at the Taman Rama Shinta Traffic Island (TITRS) in Mengwi due to physical elements that do not align with its designated function, such as seating facilities and a garden design with access from multiple directions. Meanwhile, the Taman Patung Tualen Traffic Island (TITPT) in South Kuta demonstrates a function that aligns more closely with existing regulations. These differences indicate a hypothesis that physical elements may influence the functional shift of a traffic island. This study aims to inventory existing conditions, compare the functions of TITRS and TITPT, and provide design recommendations based on regulations and user perceptions. The research method uses a survey method approach through field observation, questionnaires, and interviews. The comparison is based on three variables: function, facilities, and site character elements, with reference to the Minister of Transportation Regulation No. PM 48 of 2023. The results show that TITRS has undergone a functional shift, while TITPT continues to function as a passive traffic island. Design recommendations include limiting access and removing seating at TITRS, and improving the landscape quality of TITPT. This research is expected to serve as a reference for managers in organizing traffic islands in accordance with their intended function.